The Study of Verbal Impoliteness in the Users’ Comments of Sahamyab Stock Market Website According to Culpeper’s Theory - Shahram Naghshbandi; Hossein Razavian; Hossein Ariyaeefar (مطالعات زبانی و بلاغی)
: The phenomenon of impoliteness has always been one of the issues drawing different researchers’ attention, which hasn’t been considered as it ought to be in the Persian language. Therefore, the researchers decided to study it on a stock market website and investigate it from another perspective. This study was carried out on some of the most challenging stock market symbols having the biggest number of transactions on Sahamyab website. In this research, by analyzing about 3,600 comments equivalent to about 100,000 words, these questions were answered about how and to what extent Culpeper impoliteness models (1996, 2011) were used in the tweets of Sahamyab website users. The results indicated that almost every kind of Culpeper's impoliteness strategy was employed, with bald on-record impoliteness being the most frequent at about 34%, showing that people tend to adopt the most explicit offensive strategy to destroy the addressees' face. Mock politeness turned out second with almost 26.4%, in the form of sarcasm, irony, metaphor, and so-called dishonest politeness indicating that preserving own face when insulting others is a priority to a large number of people. Finally, negative impoliteness in conjunction with withhold politeness both amounted to 12.6% as the least frequent strategies. It could be interpreted that the main reason for the sheer volume of impoliteness and the major cause of offending individuals’ faces explicitly is the cyber relationship between the users, allowing them to hide their identity, preserve their own face, and destroy addressees’ faces with them feeling less concerned compared to face-to-face communication.